Food waste reduction in restaurants: a corporate social responsibility perspective - Silva , Alessandro Santos (2024)
The Food and Agriculture Organization (FAO) reports that 1.3 billion tons of food are lost or wasted annually. Corporate Social Responsibility (CSR) is essential in addressing this wicked contemporary problem. As demonstrated by earlier research, consumer behavior significantly affects food waste and its mitigation. Based on both these assumptions, this dissertation investigates the multifaceted issue of Food Loss and Waste (FLW) in the restaurant context, investigating both restaurant managers and consumers. This sector accounted for 14% of FLW in 2022 in Brazil (Rede PENSANN, 2022). Embedded in this context, the present dissertation aimed to respond to the following questions through three distinguished applied research: In the perspective of the prior research, what are the main determinants and outcomes of FLW? How does Corporate Social Responsibility influence the practice of food waste reduction in restaurants? How can restaurant managers act to reduce food waste? How do FLW alert messages and CSR perception affect consumers ‘leftover behavior? The combined studies revealed that restaurant management practices and consumer behavior are key FLW determinants. CSR initiatives, primarily driven by economic factors, are influenced by legal, ethical, and philanthropic considerations. Targeted messaging effectively reduces consumer waste, highlighting the importance of a multi-pronged approach to FLW reduction. This dissertation contributes to the literature by integrating diverse theoretical perspectives and offering practical recommendations for stakeholders, including restaurant managers and policymakers, to reduce FLW. Limitations include the study's specific geographic focus and the experimental study's sample characteristics; future research should explore diverse contexts and consumer segments.